Understanding Adiwiyata School Artifacts in Cultivating Students’ Characters At Madrasah Ibtidaiyah - Kholis, Nur; Indriharta, Lilik; Sholeh, Makherus; Cardoso, Luís Miguel Oliveira de Barros (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This research aims to achieve two objectives: First, to describe the types of cultural artifacts found in an adiwiyata school named MI Perwanida in Blitar, East Java. Second, to analyse the subjective interpretations of these cultural artifacts within the school context. Employing a qualitative design with a phenomenological approach, this study investigates the meaning attributed to adiwiyata artifacts in MI Perwanida. The research encompasses various artifacts within the school and the participants’ view about it, including the school principals, vice principals, teachers, students, school associations and other stakeholders. Data collection methods involve in-depth interviews, observations and documentation. Data validity is ensured through triangulation. The analysis was conducted through phases of: data presentation, data reduction and conclusion drawing. This study's findings indicate that artifacts, including written and physical objects such as photos, posters, classroom interiors, plants, bio pores, waste bins, and waste management tools, are based on religious and social values. These artifacts are construed as evocative forces, encouraging independent adoption of cleanliness habits at home and school, as well as beautification efforts. Additionally, they are seen as suggestive forces, motivating students to adopt clean behaviours, cultivate a liking for and care for plants, and develop environmental awareness. The formation of this culture reinforces Homans' theory that program realization can be analysed through activities, interactions, and emotions. The implications of this study suggest that student character formation can be intensively and consistently conducted through the implementation of an adiwiyata school. Collaboration among school stakeholders, from planning to program implementation and evaluation, is essential.